Percepção de pessoas com diabetes mellitus sobre a simulação como estratégia educativa para aplicação de insulina - Rodrigues, Jackelina de Lima (2022)
Diabetes mellitus is a metabolic disorder of heterogeneous etiologies that results in defects in insulin secretion and/or action. The application of insulin is one of the therapeutic options for the treatment of diabetes; however, its adherence has been a challenge for health professionals. Different active teaching strategies have been used for guidance on insulin application, simulation being one of them. The objective of the study was to verify the perception of people with diabetes mellitus about the simulation as an educational strategy for the application of insulin. The study was developed in a health unit in the Anhanduizinho district, in the city of Campo Grande, MS, with a descriptive quantitative approach on the knowledge of the insulin application technique and a qualitative approach, based on Bardin’s content analysis on the perception of the use of insulin simulator as a teaching strategy for insulin application. Data collection was carried out from April to June 2022, with 11 people with DM2 registered in the Hiperdia program of the health unit and it took place in three different moments: application of the sociodemographic and clinical data instrument; simulated practice and checklist for assessing the insulin application technique; application of essay questions about the perception of the use of simulation as a teaching strategy. It was observed that, currently, there is a predominantly elderly population that lives with DM for a long period and the application of insulin is part of the treatment. In the descriptive quantitative analysis, it was evidenced that the knowledge about insulin management is not fully consolidated, since the participants had failures in the stages of storage, preparation and self-administration of insulin. Regarding the perception concerning the use of the simulator as an educational strategy, two categories emerged that evidence its use as a facilitator of significant learning, a booster of self-confidence and security in the practice of insulin application. Thus, it was possible to identify that there are still gaps in knowledge regarding insulin management, however, there are active teaching strategies that have been explored with a view to education on the correct application technique. From this perspective, simulation as a teaching strategy was seen positively by the study participants and, therefore, its use in health education actions should be encouraged.